Problematika izvajanja zakona o stavki - Debelak, Marijan (Delavci in delodajalci, 2018)
The article presents some findings regarding the implementation od the Strike Act which require changes, as it is not in line with the concept of the right to strike in the Constitution and in some of the issues with the views of the supervisory bodies of the Internationa Labour Organisation and the European Social Charter. The author stems from the elements of the definition of the strike and the related issues, then proceeds to the problems regarding the issue of organisation and implementation of the strike, in particular the strikes in state bodies and public services. The article further lists some views of the case-law in assessing the lawfulness of the strikes.
Keywords: delovno pravo; elementi opredelitve; elements of definition; javni sektor in državni organi; organizacija stavke; organization of strike; public and state sector; stavke; strike